2022
DOI: 10.1097/jwh.0000000000000240
|View full text |Cite
|
Sign up to set email alerts
|

Running During Pregnancy and Postpartum, Part B: How Does Running-Related Advice and Guidance Received During Pregnancy and Postpartum Affect Women's Running Habits?

Abstract: Background: Women are unsure about the suitability and safety of running when pregnant and postpartum, with advice from medical professionals often conflicting. Aim: To explore the exercise and running-related advice pregnant and postpartum women received and the impact it has on their running habits. Study Design: Observational, cross-sectional. Methods: A total of 883 postpartum women completed an online survey. Questions were developed using pregnancy exercise guidance and clinical postpartum running … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The definition of ‘postpartum’ also varies, focusing on length of time since giving birth (eg, 12 weeks to 2 years) 36–38. The consensus that ‘postpartum’ does not refer to only the first 12 weeks after childbirth is supported by several studies using time frames >12 weeks to define their postpartum population7–9 11 12 38–43 and by evidence that postpartum mental health symptoms can still be present up to 3 years postpartum 44. The inconsistencies in the literature of how long the postpartum phase persists appear to be reflected in several time frames being identified by respondents in free-text responses and inability to reach consensus on one specific time frame.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of ‘postpartum’ also varies, focusing on length of time since giving birth (eg, 12 weeks to 2 years) 36–38. The consensus that ‘postpartum’ does not refer to only the first 12 weeks after childbirth is supported by several studies using time frames >12 weeks to define their postpartum population7–9 11 12 38–43 and by evidence that postpartum mental health symptoms can still be present up to 3 years postpartum 44. The inconsistencies in the literature of how long the postpartum phase persists appear to be reflected in several time frames being identified by respondents in free-text responses and inability to reach consensus on one specific time frame.…”
Section: Resultsmentioning
confidence: 99%
“…The perinatal period is one such transition that profoundly affects a female’s physiology and biomechanics, with lasting implications that may challenge future exercise participation 4–6. Running is a popular form of exercise for the perinatal population,7–10 but a recent study reported only 31% of pregnant or postpartum runners received advice on returning to running after childbirth 11. As a result, runners often self-determine how to continue running during and after pregnancy, and approximately 46% of runners stop running during pregnancy and 25% do not return-to-running after childbirth 12.…”
Section: Introductionmentioning
confidence: 99%
“…Another study identified that only 31% of women received broad postpartum running advice, and those that received advice were more likely to return to running. In addition, women who were made aware of return to running guidelines took longer to return to running than those who were unaware, potentially due to an increased awareness of postpartum recovery 64. Therefore, clinicians play a crucial role in encouraging physical activity in postpartum women, and informed RTA guidelines should be established to help increase a safe and equitable opportunity to return to physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, traditional return-to-sport frameworks lack female specific considerations and the inclusion of pelvic floor specialists (e.g., gynecologists or pelvic health physical therapists) within the multidisciplinary team (17). Yet, the call for recognition of PFM related symptoms within sports medicine has been established for more than a decade (8,(18)(19)(20)(21)(22)(23)(24)(25). In recent years, however, there has been greater recognition that symptoms of PFD such as pain, incontinence, or pelvic organ prolapse, negatively influence sports performance and ability to train (1,26,27).…”
Section: An Overlooked Muscle Groupmentioning
confidence: 99%